High tech sector of economy of Ukraine and Countries of the World: Condition and Tendencies of Development Высокотехнологический сектор экономики Украины и стран мира: состояние и тенденции развития - Kizim Nikolay A.; Matyushenko Igor Yu.; Cherednik Vitaliy I. (Problemi Ekonomiki, 2009)
The article considers the place of high tech sector in economies of countries of the world and dynamics of its development. the condition and prospects of development of high tech sector in economy of Ukraine are analyzed. the special attention is given to development of aircraft and space-rocket industry of Ukraine. В статье рассматривается место высокотехнологического сектора в экономиках стран мира и динамика его развития. Анализируется состояние и перспективы развития высокотехнологического сектора в экономике Украины. Особое внимание уделено развитию авиационной и ракетно-космической отраслей Украины.